Vietnam - Gas Sector Development Framework : Final Report - World Bank (Washington, DC, 2012)
Vietnam's gas sector is at a critical point. Vietnam's gas industry, from the producing field to the end-user, is already a vital component of the nation's energy economy and has the potential for major growth. Successes in the past decade have created a strong prospective demand for gas. However, Vietnam has begun to experience gas shortages. If the gas sector is to meet the rising demand for gas, there are challenges that must be addressed promptly. If certain key decisions are not made soon, these gas shortages can be expected to worsen with potentially serious economic impacts. To achieve its stated objectives for developing national gas resources, Vietnam must seek to create a 'moving train' of projects that will convert gas resources into proven reserves and production. It must also stimulate investment in the development of the requisite pipeline infrastructure as well as incentivize investment in gas consuming loads downstream such as power plants. And this will require gas pricing in consuming sectors (particularly the electricity sector) to be appropriately linked with gas pricing in the upstream gas exploration and production sector. Much remains to be done if Vietnam is to realize the potential it sees in its gas resources. This report proposes a vision, a sector framework and the sketch of a coordinated implementation roadmap for this development.